Aligning geriatric medicine fellowships with the Program of All-Inclusive Care for the Elderly (PACE). Issue 1 (2nd January 2021) - McNabney, Matthew K.; Suh, Theodore T.; Sellers, Verna; Wilner, David
ABSTRACT: Geriatric medicine fellowship programs provide comprehensive training to one-year clinical fellows and must demonstrate successful progression of competence among fellows by reporting on 23 milestones to the Accreditation Council for Graduate Medical Education (ACGME). The Program of All-inclusive Care for the Elderly (PACE) is a model of care located throughout the United States and can serve as a training venue for fellows. We surveyed 113 fellowship program directors with a response rate of 42% ( n = 48). The purpose of the survey was to assess: (1) familiarity and access to PACE and (2) perceived value of PACE to the fellowship program with regard to training and ability to achieve success in the 23 reporting milestones. Milestones involving communication and team management skills were most consistently identified as very valuable with a PACE clinical rotation. We then convened a focus group of four PACE medical directors who developed a fellowship curriculum for use in training fellows at PACE. We discuss the limitations of our design as well as the opportunities to build on the strengths of that model as a training site for fellows.